1994
DOI: 10.1021/bp00026a009
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐Cytometric Determination of the Respiratory Activity in Growing Saccharomyces cerevisiae Populations

Abstract: Flow cytometry allows one to measure relevant physical or chemical properties on a single cell, yielding the distribution of these properties in the cell population. Typically, flow cytometry has been used to determine DNA or protein distributions, but it could be extended to the determination of other relevant parameters, such as intracellular pH, membrane potential, intracellular Ca2+ concentration, mitochondrial activity, etc. In the present work, we used flow cytometry to determine the respiratory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
(22 reference statements)
0
14
0
1
Order By: Relevance
“…In general, the cytoplasmic membrane potential of microorganisms is determined by the nernstian distribution of small lipophilic charged molecules, such as tetraphenylphosphonium (TPP + ) ions (66,71), and the earlier mentioned fluorescent probes. In S. cerevisiae a good correlation was found between the specific accumulation of Rhodamine 123 in mitochondria, determined by FCM, and the respiratory activity of the cells (26,100). Kaprelyants and Kell (55) showed that by use of FCM, Micrococcus luteus cells could be divided in viable, non-viable, and non-viable but resuscitable cell populations.…”
Section: Flow Cytometrymentioning
confidence: 98%
“…In general, the cytoplasmic membrane potential of microorganisms is determined by the nernstian distribution of small lipophilic charged molecules, such as tetraphenylphosphonium (TPP + ) ions (66,71), and the earlier mentioned fluorescent probes. In S. cerevisiae a good correlation was found between the specific accumulation of Rhodamine 123 in mitochondria, determined by FCM, and the respiratory activity of the cells (26,100). Kaprelyants and Kell (55) showed that by use of FCM, Micrococcus luteus cells could be divided in viable, non-viable, and non-viable but resuscitable cell populations.…”
Section: Flow Cytometrymentioning
confidence: 98%
“…One reason for a check of the viability during cell selection is to be sure that dead cells are not selected [53]. The lipophilic cationic fluorochromes rhodamine 123 and DiOC 6 (3) (3,3'-dihexyloxacarbocyanine iodide) [54] also are used for viability tests.…”
Section: Viabilitymentioning
confidence: 99%
“…They can be incorporated by living cells of Saccharomyces cerevisiae, in which they accumulate in the mitochondria in different amounts depending on the level of the mitochondrial transmembrane potential driven by oxidative phosphorylation. These fluorochromes can be used for selective staining of mitochondria or as indicators of respiratory activity or viability in FCM [53,54] and confocal microscopy [54]. Rhodamine 123 and bis-oxonol (also known as DiBAC4 (3); which is anionic, and stains DNA, as do ethidium bromide and propidium iodide) generally are excluded by intact plasma membranes, and their uptake is sometimes used as an indicator of the death of bacteria and bacterioplankton [55][56][57].…”
Section: Viabilitymentioning
confidence: 99%
“…Individual yeast cells have been physiologically characterised by a number of authors, notably Alberghina, Mariani, Martegani, and Vanoni (1983), Block, Eitzman, Wangensteen, and Srienc (1990), Hutter and Eipel (1978), Porro, Smeraldi, Martegani, Ranzi, and Alberghina (1994), Scheper, Hoffmann, and Sch€ ugerl (1987) and Srienc (1999). However, few results have been published to date which can be used for controlling population dynamics, and even fewer which could be applied to industrial processes (M€ uller, Hutter, Bley, Petzold, & Babel, 1997;M€ uller, L€ osche, Schmidt, & Babel, 2001).…”
Section: Introductionmentioning
confidence: 99%